Efektivitas Terapi Origami dan Menggambar Terhadap Perkembangan Motorik Halus pada Anak Prasekolah di TK PKK Dewi Sartika - Delfi Marta Pratiwi; Ro’isah Ro’isah; Erna Handayani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to analyze the effectiveness of origami therapy and drawing therapy on the fine motor development of preschool children. A quasi-experimental design with a pre-test and post-test approach was applied to two intervention groups. The study involved 54 preschool children who were assigned to the origami therapy group and the drawing therapy group. Fine motor development was assessed using the Denver Developmental Screening Test II (DDST II). Data were analyzed using the Wilcoxon Signed Rank Test. The results demonstrated a significant improvement in fine motor development in both groups after the intervention (p < 0.05). Origami therapy and drawing therapy were proven effective in enhancing preschool children’s fine motor skills through stimulation of finger coordination and visual–motor integration. This study concludes that both therapies can be utilized as practical non-pharmacological interventions to support fine motor development in preschool-aged children.